Y-chromosomal genes affecting male fertility: A review - Dhanoa, Jasdeep Kaur (Vet World, 2016)
The mammalian sex-chromosomes (X and Y) have evolved from autosomes and are involved in sex determination and reproductive traits. The Y-chromosome is the smallest chromosome that consists of 2-3% of the haploid genome and may contain between 70 and 200 genes. The Y-chromosome plays major role in male fertility and is suitable to study the evolutionary relics, speciation, and male infertility and/or subfertility due to its unique features such as long non-recombining region, abundance of repetitive sequences, and holandric inheritance pattern. During evolution, many holandric genes were deleted. The current review discusses the mammalian holandric genes and their functions. The commonly encountered infertility and/or subfertility problems due to point or gross mutation (deletion) of the Y-chromosomal genes have also been discussed. For example, loss or microdeletion of sex-determining region, Y-linked gene results in XY males that exhibit female characteristics, deletion of RNA binding motif, Y-encoded in azoospermic factor b region results in the arrest of spermatogenesis at meiosis. The holandric genes have been covered for associating the mutations with male factor infertility.